A provenance study on the lapis lazuli collection from the Regional Museum of Natural Sciences in Turin. Issue 1 (1st April 2022) - Guidorzi, L; Re, A; Angelici, D; Lemasson, Q; Pacheco, C; Pichon, L; Moignard, B; Gallo, L M; Costa, E; Cossio, R; Lo Giudice, A
Abstract: Studies on the provenance of raw material used in the production of lapis lazuli artifacts can be particularly useful also in confirming or discarding the attributions given in past times by museum curators. In this work, a case study on five pieces belonging to the 19 th century "Savoy Collection" of the Regional Museum of Natural Sciences in Turin is presented. The analysis allowed to assess the correctness of a previous Chilean attribution and to assign a provenance for the whole set of samples.